DAYA HAMBAT EKSTRAK KULIT MANGGIS (Garcinia Mangostana L.) TERHADAP Streptococcus mutans (e-GiGi, 2015)
Abstract: Mangosteen fruit which in Latin is called Garcinia mangostana Linn identical with the nickname queen tropical fruit (Queen of tropical fruit) is a plant that can be utilized all its parts, including the skin of the fruit. Dental caries is an oral disease that often occurs. Streptococcus mutans is one of the causes of dental caries. This study is an experimental laboratory, using pure experimental designs (true experimental design) with a post-test only research design control design conducted in the Laboratory of Microbiology General Hospital Prof. DR. R.D. Kandou Manado in December 2014-May 2015 with research subjects using Streptoccocus mutans bacteria and as a research sample taken mangosteen peel extract (Garcinia mangostana L) were extracted using maceration method by ethanol 90%. The result showed the average broad zones of inhibition of mangosteen peel extract against Streptococcus mutans amounted at 669.42 mm2. Results of statistical calculations with independent t-test test is known that there were significant differences between groups of mangosteen peel extract and the control group (P